CHALLENGES OF EFFECTIVE IMPLEMENTATION OF THE NINE- YEAR BASIC EDUCATION PROGRAMME IN NIGERIA - Fika, Ibrahim Baba (Sokoto Educational Review, 2018)
This paper examined the challenges of effective implementation of the Nine-year Basic Education Programme in Nigeria. Eight major challenges that are considered related to the effective implementation of the nine-year programme were discussed and recommendations for improving the situation were made. These challenges are: Teacher recruitment and training, provision of instructional materials, physical facilities and equipment; Adequate funding and accountability; quality control, management of staff and pupils’ discipline, welfare support for pupils/students; enforcement of compulsory attendance; involving teachers in decision-making and community participation.